Molecular genetics, physiology and biology of self-incompatibility in Brassicaceae - WATANABE, Masao (The Japan Academy, 2012)
Self-incompatibility (SI) is defined as the inability to produce zygotes after self-pollination in a fertile hermaphrodite plant, which has stamens and pistils in the same flower. This structural organization of the hermaphrodite flower increases the risk of self-pollination, leading to low genetic diversity. To avoid this problem plants have established several pollination systems, among which the most elegant system is surely SI. The SI trait can be observed in Brassica crops, including cabbage, broccoli, turnip and radish. To produce hybrid seed of these crops efficiently, the SI trait has been employed in an agricultural context. From another point of view, the recognition reaction of SI during pollen-stigma interaction is an excellent model system for cell-cell communication and signal transduction in higher plants. In this review, we describe the molecular mechanisms of SI in Brassicaceae, which have been dissected by genetic, physiological, and biological approaches, and we discuss the future prospects in relation to associated scientific fields and new technologies.